María Celia Vázquez, Victoria Ocampo, cronista outsider, Rosario/Buenos Aires, Beatriz Viterbo, 2019, 250 páginas - Cormick, Silvina (2020)
Fil: Cormick, Silvina. Universidad Nacional de Quilmes; Argentina.